Skate! : your guide to blading, aggressive, vert, street, roller hockey, speed skating, dance, fitness training, and more - Shafran, Michael (Washington, D.C. : National Geographic, 2003)
Provides instruction in everything from standing on skates for the first time to dancing or exercising on them.
Keywords: In-line skating -- Juvenile literature; Extreme sports -- Juvenile literature; In-line skating; Roller skating; Extreme sports